Use of aceclofenac (aertal) in back pain - Yuliya Leonidovna Korsakova; Yulia Leonidovna Korsakova (Современная ревматология)
Back pain is a generalized type of locomotor lesion that is caused by soft tissue pathology and degenerative changes in the vertebral column in most cases and by intervertebral disk herniation, spinal stenosis, compression fractures in osteoporosis, by injuries, congenital anomalies, vertebral displacement less frequently, as well as by infections, tumors, inflammatory processes in the vertebral column, and related pain. A number of rheumatic diseases, including seronegative spondylarthritis, Scheuermann-Mau' disease, Forestier's disease, osteoarthrosis, etc., are accompanied by back pain. The cause of back pain syndrome cannot be frequently identified. This abnormality is treated by nonsteroidal antiinflammatory drugs, among which aceclofenac (Aertal) has acquired a reputation as an agent having a good tolerability.